Cultural Revolution in the Philippines amidst the New Normal - Lisette Luy Ong (International Journal of Qualitative Research, 2022)
Comparison between Cultural Revolution in China and the need to bring back Generation Z to the grassroots level, especially after the ill effects brought about by the pandemic. The transition to bringing everything back to normal will be a very difficult task even with the implementation of the limited face-to-face since April 4. Since this study is qualitative, the weight will be geared towards a comparison of the values and practices absorption pre-digital age and the digital age, Admittedly, there have been unfilled gaps in the abrupt turnout from carefree and laidback teenagers to being digital natives. The results of the study show that there are unexpected situations that can compromise not only the teachers but more of the students so with the other stakeholders.